2015
DOI: 10.1002/acr.22598
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Efficacy of Switching From Intravenous to Subcutaneous Tocilizumab Monotherapy in Patients With Rheumatoid Arthritis

Abstract: ObjectiveTo evaluate the efficacy and safety of switching from intravenous (IV) tocilizumab (TCZ) to subcutaneous (SC) TCZ monotherapy in rheumatoid arthritis patients.MethodsPatients who had completed 24 weeks of TCZ‐SC (162 mg/2 weeks) or TCZ‐IV (8 mg/kg/4 weeks) monotherapy in the double‐blind period of the MUSASHI study were enrolled in an 84‐week open‐label extension period. All received TCZ‐SC (162 mg/2 weeks) monotherapy. Effects of the IV to SC switch were evaluated at week 36 (12 weeks after switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
(32 reference statements)
3
27
0
Order By: Relevance
“…Similar results were observed in the 84-week open-label extension period of the phase III MUSASHI study, as well as in a real-world comparison of DAS28-ESR clinical response in patients at baseline and 3 months after switching from TCZ-IV to TCZ-SC [18,19]. TCZ-SC potentially reduced disease activity in TCZ-naïve patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar results were observed in the 84-week open-label extension period of the phase III MUSASHI study, as well as in a real-world comparison of DAS28-ESR clinical response in patients at baseline and 3 months after switching from TCZ-IV to TCZ-SC [18,19]. TCZ-SC potentially reduced disease activity in TCZ-naïve patients.…”
Section: Discussionsupporting
confidence: 81%
“…In the phase III SUMMACTA study, the efficacy and safety profiles in patients who switched from TCZ-IV in combination with csDMARDs to TCZ-SC were comparable with those in patients who maintained TCZ-IV [13,17]. Similar results were observed with TCZ monotherapy in the phase III MUSASHI study, in which patients who received TCZ-IV monotherapy and switched to TCZ-SC monotherapy experienced efficacy and safety comparable with those in patients who received TCZ-IV monotherapy [18]. However, data from these clinical trials may not fully represent the safety and effectiveness of TCZ-SC in patients in real-world clinical settings.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…A subanalysis of patients in the 84-week open-label period of the MUSASHI trial who switched from TCZ-IV q4w to TCZ-SC q2w showed that efficacy was maintained; however, the response rate for remission was decreased in patients with high body weight (!70 kg), which correlated with lower TCZ serum trough levels [11]. During the MUSASHI open-label period, patients with an inadequate response to TCZ-SC q2w could have their dosing interval shortened and receive TCZ-SC qw, which resulted in increased TCZ serum trough levels and improved efficacy with a comparable safety profile [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have shown the safety and efficacy profile of TCZ-SC to be comparable to that of TCZ-IV 7 . Switching from TCZ-IV to SC was shown to be generally successful and sustained over time 8 . A recent study analyzed clinical data from 58 patients with RA who switched from TCZ-IV to TCZ-SC, suggesting that the switch in realworld settings is effective and can be considered for convenience 9 .…”
Section: To the Editormentioning
confidence: 99%